Determinants of corporate cash holdings: Evidence from Portuguese publicly traded firms - Fernandes, Filipa; Coelho, Luís; Peixinho, Rúben M.T. (Dos Algarves, 2017)
This paper investigates the determinants of cash holdings of publicly traded Portuguese firms. We find that such firms hold less cash than similar companies operating in countries where both shareholders and creditors’ rights are more tightly protected by the law. In addition, our regression results suggest that leverage, other liquid assets, and firm growth are negatively correlated with our sample firms’ cash holdings whereas long-term debt and financial distress are positively correlated. Our findings cannot be reconciled with just one of the existent theories (trade-off, pecking order and free cashflow theory), and emphasize the importance of a country’s legal, institutional, and economic environment for explaining firms’ cash holdings decisions.